2022
DOI: 10.3390/cancers14133061
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Immune and Metabolic Microenvironment Is Associated with the Post-Operative Relapse in Stage I Non-Small Cell Lung Cancer

Abstract: The underlying mechanism of post-operative relapse of non-small cell lung cancer (NSCLC) remains poorly understood. We enrolled 57 stage I NSCLC patients with or without relapse and performed whole-exome sequencing (WES) and RNA sequencing (RNA-seq) on available primary and recurrent tumors, as well as on matched tumor-adjacent tissues (TATs). The WES analysis revealed that primary tumors from patients with relapse were enriched with USH2A mutation and 2q31.1 amplification. RNA-seq data showed that the relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Lung cancer mortality accounts for 27.05% and 22.42% of urban and rural tumour mortality, respectively [ 18 ]. Conventional chemotherapy has a 25% to 35% near-term remission rate for advanced non-small-cell lung cancer (NSCLC), a median survival time of 8 to 11 months, a one-year survival rate of only 30%, and an overall 5-year survival rate of less than 2% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer mortality accounts for 27.05% and 22.42% of urban and rural tumour mortality, respectively [ 18 ]. Conventional chemotherapy has a 25% to 35% near-term remission rate for advanced non-small-cell lung cancer (NSCLC), a median survival time of 8 to 11 months, a one-year survival rate of only 30%, and an overall 5-year survival rate of less than 2% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA-and RNA-based next-generation sequencing. Whole exome and transcriptome sequencing were performed in Geneplus-Beijing (Beijing, China) as previously described [27][28][29] . Brie y, genomic DNA and RNA were extracted from the tumor samples using FirePureTM FFPE gDNA Extraction Kit for genomic DNA and RNeasy FFPE Kit for RNA or AllPrep DNA/RNA FFPE Kit for both DNA and RNA (QIAGEN, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Due to a scarcity in literature and lack of precise prognosis, improving the understanding of genetic markers is necessary. Here, we present two cases of PitNET undergoing genomic and transcriptomic analysis of tumour mass and peripheral blood by WES and RNA sequencing ( Chen et al, 2021 ; Zhang et al, 2022 ; Zhou et al, 2022 ). It was found that the overexpression of LAG3 and somatic mutations in DICER1 may be accountable for tumorigenesis and metastasis.…”
Section: Introductionmentioning
confidence: 99%